Getting more unequal: Rising labor market inequalities among low-skilled men in West Germany. (March 2015) - Giesecke, Johannes; Heisig, Jan Paul; Solga, Heike
Highlights: Labor market inequalities among low-skilled West German men have increased. To shed more light on this trend, we employ a reweighting strategy and regression models. We examine the contributions of worker/workplace characteristics to these trends. Results show a growing insider–outsider divide among low-skilled men. Abstract: During recent decades, earnings differentials between educational groups have risen in most advanced economies. While these trends are well-documented, much less is known about inequality trends within educational groups. To address this issue, we study changes in labor market inequalities among low-skilled men in West Germany. Using data from the German Socio-economic Panel, we show that both risks of labor market exclusion and earnings dispersion have grown dramatically since the mid-1980s. We consider possible explanations for these trends, drawing on an analytic distinction between compositional changes with respect to worker/job characteristics and changes in the effects of these characteristics on labor market outcomes. Using a reweighting strategy and regression models, we find that both compositional trends and changes in the effects of important characteristics have contributed to the observed increase in labor market inequalities. We discuss the likely influence of German welfare state programs, labor market regulation, and of recent changes in these domains, and sketch promising avenues for future research.